Gene expression patterns of cheek, gum and tongue squamous cell carcinoma / Amyza Mohammed Saleh - Mohammed Saleh, Amyza (2012)
Clinical evidence suggested that biological behavior as well as response to treatment is different in OSCC arising from the different anatomical locations of the mouth and could be influenced by the activation or/and inactivation of different genes and pathways. Objective: Gene expression analysis of OSCC from different sites of the oral cavity was conducted to determine if there were significant differences in the expression pattern that could be associated with clinical observations. Materials and Methods: Formalin-fixed paraffin-embedded tissues from OSCC from cheek, gum, tongue and non-cancerous oral mucosal from the matching sites were used in microarray experiments (DASL, Illumina) to determine the gene expression patterns. Microarray data were analysed using Genespring to identify differentially expressed genes and these changes were validated using quantitative polymerase chain reaction and immunohistochemistry. The role of specific genes in driving OSCC were determined using cell lines genetically modified to exogenously express these genes. Results: This study demonstrated that FFPE tissues can be used for microarray experiments. Differentially expressed genes in OSCC were identified and their expressions were validated in independent samples. Principal Component Analysis demonstrated that different sites of OSCC have distinct gene expression profiles. Genes that were commonly altered in all sites and those that were distinct to a particular site were identified. Focusing on a gene FOLR1 that was found to be enriched in OSCC of the tongue, exogenous expression of this gene was shown to promote migration and invasion. Conclusion: This study suggests that the genetic progression of OSCC in the different sites is distinct, thus cautioning the generalization of OSCC when identifying biomarkers for diagnosis, prognosis and therapy. Furthermore, specific genes may confer different cancer traits that may explain the clinical differences seen in the different sites of OSCC.